THE PRINCIPLES OF THE DE POUVOIR DETOURNEMENT ON THE ACTION OF SOE OFFICERS THAT AFFECT STATE LOSSES IN REGULATION NUMBER 17 OF 2003 CONCERNING STATE FINANCE: PENERAPAN PRINSIP DETOURNEMENT DE POUVOIR TERHADAP TINDAKAN PEJABAT BUMN YANG MENGAKIBATKAN KERUGIAN NEGARA MENURUT UNDANG-UNDANG NOMOR 17 TAHUN 2003 TENTANG KEUANGAN NEGARA - Arifin, Muhammad Zainul; Muntaqo, Firman (Nurani, 2018)
To this day loss of state enterprises company ( BUMN ) still a problem absolutely crucial . In 2018 exists 22 State-owned business entities (BUMN) Who has lost up to 5,4 million. While 22 State-owned business entities Has raised its capital participation the state piety (PNM) To be able to run the business as well as possible . In his loss State-owned business entities (BUMN) Often defined as losses to the state . But the state is not a state a loss . In general the definition of losses to the state contain a major illegal actions . illegal actions in perspective contains the things that are causing the cash , securities , or the reduced state credit . In other words the state losses referred to are formil loss in meaning .For what is in soe is their countries to have separated